A systematic review of constitutional regulation of martial law and its impact on citizens’ rights - Romanenko, Kateryna; Chmielarz, Patryk; Taran, Dmytro; Kuryliuk, Yurii; Pelekh, Iia (Global Prosperity, 2025)
Abstract. The purpose of this study is to examine the constitutional and legal mechanisms for restricting human rights under martial law in Ukraine, with a specific focus on ensuring the proportionality, legality, and necessity of such restrictions. The research employs doctrinal legal analysis combined with comparative legal methodology to evaluate the national constitutional framework in relation to international standards for the protection of human rights during a state of emergency. The findings indicate that the mechanism for restricting human rights under martial law requires more precise legislative regulation to ensure alignment with constitutional guarantees and to prevent potential abuses. While the legislation governing martial law in Ukraine includes general provisions on permissible restrictions, it lacks detailed procedural safeguards necessary to protect the core essence of fundamental rights. The analysis further reveals that the effective exercise of the right to judicial protection is impeded by limited access to courts, shortened procedural timelines, and restrictions on court operations in areas affected by active hostilities. Moreover, the study finds that the constitutional complaint mechanism, although significant, remains underutilized. Enhancing its practical effectiveness necessitates simplification of the procedural requirements. These results are consistent with prior research underscoring the imperative of preserving the substance of constitutional rights even during wartime and ensuring effective judicial protection for citizens. Overall, the study underscores the necessity of enhancing constitutional and legislative mechanisms to maintain a proper balance between state security interests and the protection of individual rights under martial law. Strengthening these mechanisms would contribute to reinforcing constitutionalism and the rule of law in Ukraine during times of crisis.